2016
DOI: 10.1371/journal.pone.0148562
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Transcriptional Responses to Mastitis-Causing Escherichia coli

Abstract: Bovine mastitis is a widespread disease in dairy cows, and is often caused by bacterial mammary gland infection. Mastitis causes reduced milk production and leads to excessive use of antibiotics. We present meta-analysis of transcriptional profiles of bovine mastitis from 10 studies and 307 microarrays, allowing identification of much larger sets of affected genes than any individual study. Combining multiple studies provides insight into the molecular effects of Escherichia coli infection in vivo and uncovers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…A previous study identified genes involved in response to bacterial lipopolysaccharide (LPS), the major component of the outer membrane of Gram-negative bacteria, in a mouse mammary gland model of mastitis [ 28 ]. A similar model of mastitis has also been implemented in dairy cattle [ 29 31 ]. We reasoned that genes involved in mastitis susceptibility would likely be constitutively expressed in the mammary gland and immune tissues and/or differentially expressed in sheep bone marrow-derived macrophages (BMDMs) in response to LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study identified genes involved in response to bacterial lipopolysaccharide (LPS), the major component of the outer membrane of Gram-negative bacteria, in a mouse mammary gland model of mastitis [ 28 ]. A similar model of mastitis has also been implemented in dairy cattle [ 29 31 ]. We reasoned that genes involved in mastitis susceptibility would likely be constitutively expressed in the mammary gland and immune tissues and/or differentially expressed in sheep bone marrow-derived macrophages (BMDMs) in response to LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, based on our results, E . coli infection causes down-regulation of genes encoding lipid biosynthesis enzymes including ALOX15 , FASN , GPAM , TM7SF2 that are involved in milk production [ 37 ]. Generally, in infection, host metabolism is suppressed because the tissue has to divert energy to fight infection.…”
Section: Discussionmentioning
confidence: 99%
“…coli and Staphylococcus aureus strains infections and also between lipopolysaccharide (LPS), and E . coli -induced mastitis [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…coli or S . aureus IMIs were lately demonstrated to be very contrasting [38,39], at least partly because of the high inflammatory response to LPS found in Gram negative bacteria [40], whereas S . aureus can modulate and subverts host responses by suppressing pro-inflammatory pathways [41].…”
Section: Discussionmentioning
confidence: 99%